Strengthening the Reporting of Genetic Risk Prediction Studies: The GRIPS Statement (Italian Journal of Public Health, 2012)
The rapid and continuing progress in gene discovery for complex diseases is fuelling interest in the potential application of genetic risk models for clinical and public health practice. The number of studies assessing the predictive ability is steadily increasing, but the quality and completeness of reporting varies.A multidisciplinary workshop sponsored by the Human Genome Epidemiology Network developed a checklist of 25 items recommended for strengthening the reporting of Genetic RIsk Prediction Studies (GRIPS), building on the principles established by prior reporting guidelines.These recommendations aim to enhance the transparency of study reporting, and thereby to improve the synthesis and application of information from multiple studies that might differ in design, conduct or analysis.A detailed Explanation and Elaboration document is published separately in PLoS Medicine as Supporting Information (S1) and in Janssens AC, Ioannidis JP, van Duijn CM, Little J, Khoury MJ; GRIPS Group. Strengthening the reporting of genetic risk prediction studies: the GRIPS statement. Eur J Epidemiol 2011; 26(4): 255-9....
Keywords: Genetic risk models; GRIPS